Research in Afghanistan: Innovative Strategies for Overcoming Methodological Challenges (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
This paper examines challenges associated with conducting social science research in third world, conflict settings. Employing a qualitative, case study approach, we highlight the methodological barriers confronted by administration of Afghanistan Research Services (a Division of Afghanistan Holding Group) Mortgage Market Assessment, a study conducted in five major Afghanistan cities. While these barriers may be viewed through the lens of western social science as threatening the validity of legitimate research, innovative accommodations in the areas of sampling, quality control and mitigation of fear and mistrust led to successful data collection efforts. This case study of research in Afghanistan, offers lessons for ambitious researchers interested in adapting standard research techniques to future work with non-western peoples living under conflict conditions